Using GPM and BMKG Satellite Rain Data for Compiling Intensity-Duration-Frequency (IDF) Curves in the Residential Area of Medan Marelan District - Hanova, Yudha; Sari, Kartika Indah; Regina, Pramesti (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
Medan Marelan District is a densely populated residential area with an area of 4.20 km2. This area often experiences flooding, particularly during the rainy season. Flooding is caused by water resource infrastructure buildings that do not function optimally, so runoff is not distributed properly. This study aims to compile an IDF curve using Global Precipitation Measurement (GPM) satellite data and the Meteorology, Climatology, and Geophysics Agency (BMKG). The IDF curve informs the pattern and characteristics of regional rainfall so that it can be the basis for the planning and evaluation of water resource infrastructure buildings in residential areas. The compilation of the IDF curve started with the validation of the maximum daily rainfall data for 10 years (2014–2023) using the double mass curve method to ensure the consistency and accuracy of the rainfall data from the GPM and BMKG satellites. After data validation, a frequency analysis was performed to determine the probability distribution that matches the characteristics of the rainfall data. The statistical parameters analyzed included the average daily maximum rainfall, standard deviation, skewness, and kurtosis. Furthermore, the Goodness-of-Fit test using the Smirnov-Kolmogorov method was conducted to evaluate the suitability of the probability distribution (Normal, Log-Normal, Gumbel, or Log Pearson III) with the observed rainfall data. The best probability distribution was used to determine the return period rainfall intensity. The analysis results showed that the Log Pearson III distribution was the best distribution for rainfall in the Medan Marelan District. The IDF curve shows the pattern of rainfall intensity and duration for 24 h, with the peak of rainfall intensity and duration occurring in the 6th hour.